Cyberloafing Behavior: The Determinant Factors Related to Work Stress and Workload in The Banking Sector - Novianti, Khusnul Rofida; Roz, Kenny (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Cyberloafing is a recent organizational behavior that arises due to easy access to the internet, allowing employees to use company-provided internet facilities for non-work-related activities. Previous researches have attempted to identify variables that influence cyberloafing, including work stress and workload. The purpose of this study was to examine the impact of workload dimensions (psychological workload and physical workload) on cyberloafing behavior, mediated by work stress, within the banking sector of Malang City. This study uses an explanatory quantitative approach with data collection methods through online questionnaires . The responses of 148 participants are analyzed using Partial Least Square (PLS) analysis. The result shows that workload does not significantly affect cyberloafing behavior. However, workload does have a positive and significant influence on work stress, which in turn positively and significantly affects cyberloafing behavior. Work stress acts as a mediator between workload and employee cyberloafing behavior in the banking sector of Malang city. Furthermore, the study highlights the benefits of regular breaks from work in the form of cyberloafing, as it allows employees to recharge their energy and serves as an effective defense against workplace stress. Keywords: banking, behavior, cyberloafing, workload, work stress